Academic seminars as tool for clinical and translational science education and dissemination: Perceptions and priorities in the COVID‐19 era - Katherine L. Chen; Carlos Irwin A. Oronce; Nancy E. Calderón; Katherine L. Kahn (Wiley, 2024)
Abstract Academic seminars are an important venue through which investigators in health services research (HSR) and other clinical and translational science disciplines can share their work, gather feedback, and connect with colleagues. However, the format and focus of these seminars shifted abruptly when the coronavirus disease 2019 (COVID‐19) pandemic necessitated social distancing and underscored the salience of health equity. Little is known about how contemporary academic seminars are meeting the evolving needs of the HSR community. We surveyed 2021-2022 participants in a virtual HSR seminar series to understand experiences of and priorities for the seminars. We also compared results stratified by self‐reported under‐represented minority (URM) status. Of 45 respondents (including 26 faculty members, 8 trainees, 9 staff members, and 2 community partners), 38% self‐identified as URM. Participants reported high satisfaction with seminar quality, diversity of topics, and audience participation (median ≥4 for all outcomes in Likert‐scaled items where 5 = very satisfied). Knowledge acquisition, understanding of research methods, and collaboration were commonly cited as benefits of seminar attendance. Implementation science content and external collaboration were most often endorsed as priorities for future seminars. URM participants were over three times more likely than non‐URM participants to cite learning about engaging community stakeholders and historically excluded populations as a benefit of seminar participation. Virtual academic seminars can be an effective modality for knowledge sharing and collaboration worth continuing after COVID‐19 restrictions are lifted. Emphasizing equity, diversity, and inclusion (EDI) values in these seminars may hold potential for advancing academic departments' own EDI goals.